Claudio Gutiérrez: At the Dawn of Artificial Intelligence - Carvajal Villaplana, Álvaro (2024)
In this article we present and analyze some of Gutierrez’s more relevant ideas related to the possibility of machine thinking, in particular his replies to the objections raised by Searle and Penrose. The notion of algorithm is explained, as well as its relevance for computer science, robotics and artificial intelligence. We consider the scientific status of this field as defended by the author. Lastly, we pose some social problems that informatics and artificial intelligence may give rise to.